Emerging Roles of Plant Circular RNAs - Qinjie, Chu; Enhui, Shen; Chu-Yu, Ye; Longjiang, Fan; Qian-Hao, Zhu (Journal of Plant Cell Development, 2018)
Circular RNAs (circRNAs) are covalently closed single-stranded loop RNA molecules with or without protein coding capability. CircRNAs were previously considered to be splicing intermediates or artifacts but are now found to be pervasively expressed in all eukaryotes studied with some demonstrated to have important molecular functions in various biological processes. CircRNA is now a hot study topic of molecular biology. In this review, we summarize the progress achieved so far on plant circRNAs, including identification and functional characterization, compare the similarities and differences of circRNAs between plants and animals, and discuss the challenges for confident detection and functional investigation of plant circRNAs. Similar to what have been found in animals, plant genomes contain a large number of circRNAs that potentially regulate a wide range of biological progresses related to plant development and biotic/abiotic responses. Despite only a few plant circRNAs have been functionally characterized, novel function/mechanism that has not been reported in animals was revealed, implying more exciting findings about plant circRNAs are expected in future studies.
Keywords: Circular RNAs; identification; function; alternative splicing; circularization